Judge Barker and the Vengeance of "Bloody Bill" - Michael Shimeall (Symphony in the Flint Hills, 2012)
In the early pre-statehood history of the Neosho Valley, few events have rivaled that of the death of A.I. Baker. Histories state that his death at the hand of “a gang of pro-slavery bandits” led by the notorious confederate guerilla and Quantrill raider
Keywords: Blood Bill; vengeance; violence; chaos; confederate; guerilla; Quantrill; Civil War; murder; Council Grove; Sac and Fox; Indians; Judge Baker; Neosho; Rock Creek; Kaw Indian Mission; Breckinridge County; Bleeding Kansas; Americus; Emporia; pro-union; pro